Resenha Crítica - Dante Mendes Aldrighi (Universidade de São Paulo, 1993)
MARGLIN, Stephen. What do bosses do? The origens and functions of hierarchy in capitalist production. In: GORZ, Andrè (org.), The division of labor. Sussex: Harvester Press, 1978, p. 13-54.